The Effect of Density on Onion Yield in Mono-Cropping and Intercropping with Fenugreek - Tahereh Moghbeli (Journal of Agricultural Science and Sustainable Production, 2017)
In order to investigate the of effect intercropping on yield and yield components of onion (Allium cepa L.)  and fenugreek (Trigonella foenum-graecum L.), a  factorial experiment was carried out based on completely randomized block design with three replications at the research field located in south of Kerman, Iran. The first factor was onion density (20- 25 and 30 plant.m-2) and the second factor was fenugreek plant density (12- 15 and 25 plant.m-2) and sole culture of plants with aforementioned densities were considered. After harvesting the number leaves and length of plants, fresh and dry weight, bulb diameter, fresh and dry weight of bulb, Land Equivalent Ratio (LER) and Relative Value Total (RVT) was measured. The results showed that the highest yield of onion (43.2 t.h-1) was obtained from 20 plant m-2. In intercropping treatment number of leaves, plant length, bulb fresh and dry weight was increased by decreasing plant density from 20 to 30 plant m-2. The  highest fresh and dry weigh of onion bulb (167.2 and 11.64 g) was  produced in 20  plant.m-2. Number leaf and length of the plant and fresh and dry weigh of onion was increased in intercropping. However intercropping fenugreek with onion had no significant effect on its yield in comparison with mono culture. The highest Land Equivalent Ratio (LER) (1.65) and Relative Value Total (RVT) (1.72 (was recorded  in 30 plant.m-2 onion and 12 plant.m-2 fenugreek and 30 plant.m-2 onion and 25 plant.m-2 fenugreek combination culture respectively.